Paradigma Baru dalam KUHP 2023: Tinjauan Politik Hukum dan Analisis Kebahasaan - Arni, Irma Lida (AGUSPATI RESEARCH INSTITUTA, 2025)
The enactment of Indonesia’s 2023 Criminal Code (KUHP) marks a new phase in the nation’s legal history. This reform does not merely replace colonial penal provisions but represents a paradigm shift toward a more humanistic and nationally oriented system of justice. This study examines the reform through two lenses: legal politics and linguistic analysis. Using a qualitative-descriptive approach, it explores both the normative substance of the new KUHP and the linguistic features that reflect a progressive legal ideology. Findings indicate that the reform embodies Indonesia’s legal decolonization by shifting the philosophy of punishment from retribution to restoration. Linguistically, the new KUHP demonstrates more communicative, inclusive, and persuasive patterns in diction, syntax, and pragmatics, transforming the law into a discursive medium that fosters public awareness. Legal language designed to be more communicative, precise, and participatory, embodying substantive justice and Pancasila values.